Perilaku Produsen pada Model Kemitraan Go Food dalam Prespektif Ekonomi Islam (studi kaasus Daerah Wirobrajan,Yogyakarta) - Meita Masfufah; Siti Achiria (JESI (Jurnal Ekonomi Syariah Indonesia), 2019)
Producer behavior is a company that helps increase the value of goods or services that produce consumption needs, partnership is cooperation between two parties with equal and mutually beneficial needs. The study aims to review how the partnership model between food producers and parties go food gojek, the research method used is qualitative descriptive by collecting and interviewing Go Food partners in the Wirobrajan area of Yogyakarta, producers feel greatly helped by becoming partners Go food Which experience Riding in sales, can help market their stalls online. Read more about distributing faster and free to customers themselves to buy products from suppliers without having to come to the shop.Key : producer behavior, patnership, Go Food